1988
DOI: 10.1111/j.1476-5381.1988.tb16555.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of neuropeptide‐induced histamine release from human dispersed skin mast cells

Abstract: 1 Human skin mast cells, unlike other human mast cells so far studied, released histamine in a concentration-related manner in response to substance P, vasoactive intestinal peptide (VIP) and somatostatin (1 yM to 30 yM). In contrast, eledoisin, physalaemin, neurokinin A, neurokinin B, calcitonin gene-related peptide (CGRP), neurotensin, bradykinin and Lys-bradykinin induced negligible histamine release. 2 The low histamine releasing activity of physalaemin, eledoisin, neurokinin A and neurokinin B relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
104
1
7

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(115 citation statements)
references
References 27 publications
3
104
1
7
Order By: Relevance
“…These stress-induced morphological changes are prevented by central and peripheral administration of an NK-1 receptor antagonist. Together with the observations that mast cells are closely apposed to SP-containing nerve terminals and that mast cell secretion is elicited by SP [26,32,33], this evidence suggests that stress-induced release of SP may induce morphological changes in the bladder wall that are characteristic of IC.…”
Section: Discussionmentioning
confidence: 83%
“…These stress-induced morphological changes are prevented by central and peripheral administration of an NK-1 receptor antagonist. Together with the observations that mast cells are closely apposed to SP-containing nerve terminals and that mast cell secretion is elicited by SP [26,32,33], this evidence suggests that stress-induced release of SP may induce morphological changes in the bladder wall that are characteristic of IC.…”
Section: Discussionmentioning
confidence: 83%
“…We have previously reported that intradermal injection of endothelin-1 into the human forearm induces a vasoconstrictor response at the site of injection and a surrounding axon-reflex flare due to increased cutaneous blood flow (Brain et at., 1989;Crossman et at., 1991 (Benyon et al, 1987;El Lati et al, 1991;Lowman et al, 1988). However, platelet activating factor (PAF), which also causes an H1-receptor antagonist sensitive flare (Archer et al, 1985), does not release histamine from skin mast cells in vitro (Thomas & Church, 1990) suggesting that PAF stimulates mast cells by an indirect mechanism in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Rat peritoneal mast cells are a model system for the study of human skin mast cells as both cells respond to both IgE receptor-dependent and non-immunologic stimuli (7). The mast cell line RBL-2H3 is a model with which to study IgE-dependent signal transduction.…”
mentioning
confidence: 99%